Barriers to domestic retrofit quality: Are failures in retrofit standards a failure of retrofit standards?. Issue 3 (March 2022) - Fylan, Fiona; Glew, David
Thermal retrofits of homes are central to the UK's fuel poverty and net zero carbon policies but there are concerns about poor quality installation and so new standards are to be introduced (PAS2035). We have explored retrofit installers' perceptions of the barriers to installing internal wall insulation (IWI) and of current regulations and standards for retrofits. We conducted four focus groups with retrofit installers. Thematic analysis identified three themes. (1) IWI is viewed as impractical in situations other than new builds, extensions and conversions as it is too time-consuming and expensive. (2) Installing IWI is perceived as an unskilled job with no need for training or referring to standards during installation. (3) Because standards lack credibility, installers can be sceptical of potential problems caused by on-site installation adaptations, for example thermal bridging. Our results show that retrofit standards have not improved retrofit quality. Awareness and credibility of standards is low, and new standards (PAS2035) will introduce additional costs which may reduce the pool of installers willing to engage in the retrofit market. Policies need to address installer training, professional identity and social practices, and reduce barriers to change in order to increase success.